5 Restricted visiting and gender influence perceptions about end-of-life care support: a national UK survey of bereaved relatives' views. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Mayland, Catriona R; Hughes, Rosemary; Mcglinchey, Tamsin; Donnellan, Warren; Bennett, Kate; Dalton, Louise; Rapa, Elizabeth; Lane, Steven; Mason, Stephen
Abstract : Background: The COVID-19 pandemic significantly affected experiences of death and dying for patients and families. Our focus was on bereaved relatives' perceptions about experiences of care in the last days of life during the pandemic to help inform practice and policy. Methods: A national online survey, informed by patient and public involvement, was developed and disseminated via social media, public and professional networks between June and October 2020. Validated instruments (e.g. abbreviated 'Care Of the Dying Evaluation' questionnaire) and purposively designed questions were used to assess the impact of COVID-19. Data was analysed using descriptive statistics, logistic regression and thematic analysis of free-text responses. Results: Respondents (n=278) had a mean age of 53.4 years (range 19–68); 216 (78.0%) female and 174 (62.6%) 'son/daughter' to the deceased. Over half (156, 56.5%) were unable to visit during the dying phase. Almost 70% of the deceased (mean age 80.5 years; 160 (57.6%) female) died in their 'usual place of care' (home n=30 (10.8%); nursing home n=162 (58.3%)). This was perceived as the 'right place' by 176 (75.2%) respondents. Positive perceptions were reported about nursing care compared with medical care. Unmet support was reported: 71 (30.1%) rated emotional support as 'poor'; 110 (45.5%) perceived they were inadequately supported prior to death. Being a male respondent (OR 2.9, p=0.03) and able to visit during the last days of life (OR 2.2, p=0.04) were independently associated with perceptions about being adequately supported. Corresponding free-text analysis suggested 'not knowing' about care was especially distressful; 'clear, compassionate leadership' contributed to positive experiences. Conclusions: Capturing these experiences during the height of the first COVID-19 wave is pertinent to inform measures to enhance care. Disconnection between dying patients and families is a key area to be addressed and the challenge of balancing individual and societal needs to enable high quality end-of-life care.